Is the secular trend reflected in early stages of human ontogenesis? - Domagała, Zygmunt; Dąbrowski, Paweł; Porwolik, Michał; Porwolik, Krystian; Gworys, Bohdan (Anthropological Review, 2014)
There are a limited number of studies on secular changes in the neonatal period, and the majority of them concern research related to childhood and puberty The objective of our study was to carry out a comparative analysis of body weight and length at birth in neonates born in Wrocław in subsequent decades since 1950 to find out if these parameters are subject to secular trend, and what values they attained during the studied period of 50 years. The study was carried out in the 1950s, 1960s, 1970s, 1980s, 1990s and in 2000 to analyse changes in body length, body weight and Rohrer index over time. The sample studied consisted of 7510 neonates, 3882 males and 3628 females, born in Wroclaw. Secular changes were tested using one-way variance analysis. The values of F statistics were compared to the critical values of the F Snedecor distribution. Changes in the features of neonates in subsequent study years were analysed using the modified z-score. Data were normalised for standard deviation in decade increments. Results demonstrated very slight, though statistically insignificant increase in body weight at birth. Over the 50-year period the mean body weight of neonates was in the range of 3.3–3.4 kg, regardless of sex. Results demonstrated very slight, though statistically insignificant increase in body weight at birth. Over the 50-year period the mean body weight of neonates was in the range of 3.3–3.4 kg, regardless of sex. The acceleration in the body length of neonates caused a gradual decrease in the mean values of the Rohrer index. No secular trend in body weight was found in Wrocław neonates over the 50-year period between 1950 and 2000 With regard to body length at birth, four waves of deceleration and acceleration were found: period 1 (1950s): deceleration in the increase of the analysed body parameters of neonates; period 2 (1960s): acceleration in neonates’ growth; period 3 (1970s and 1980s): economic crisis and political transformations in Poland; this is reflected by the stable mean values of body dimensions in neonates. The secular trend clearly decelerated, and period 4 (1990s and 2000) – very intense acceleration in both body weight and length and the Rohrer index.